Targeting the MEK1/2 pathway to combat Staphylococcus aureus infection and inflammation in cystic fibrosis - Eryn Zuiker; Gregory Serpa; Mithu De; Yiwei Liu; Daniel J. Wozniak; Kymberly M. Gowdy; Jean Charron; Susan E. Birket; Megan R. Kiedrowski; Emily A. Hemann; Matthew E. Long (mBio)
ABSTRACT Staphylococcus aureus infections remain an ongoing challenge for people with cystic fibrosis (PwCF), with the increased global prevalence of multidrug-resistant strains requiring new therapeutic approaches. Our previous studies demonstrated anti-inflammatory effects of several MEK1/2 inhibitor compounds, including PD0325901, CI-1040, and trametinib, in human phagocytes from PwCF and a murine S. aureus pulmonary infection model (M. De, G. Serpa, E. Zuiker, K. B. Hisert, et al., Front Cell Infect Microbiol 14:1275940, 2024, https://doi.org/10.3389/fcimb.2024.1275940). A recently developed MEK1/2 inhibitor compound, ATR-002, has been recognized for its ability to exert direct antibacterial effects on gram-positive bacterial species, including S. aureus (C. Bruchhagen, M. Jarick, C. Mewis, T. Hertlein, et al., Sci Rep 8:9114, 2018, https://doi.org/10.1038/s41598-018-27445-7). However, whether ATR-002 elicits antibacterial effects on clinically relevant strains of S. aureus or anti-inflammatory effects is unknown. In this study, the effects of ATR-002 on human CF macrophage TLR2-induced pro-inflammatory cytokine secretion were evaluated, demonstrating that ATR-002 reduced TNF-α and IL-8 secretion induced by the TLR2 agonists FSL-1 or Pam3CSK4. The antibacterial effects of ATR-002 were evaluated by minimum inhibitory concentration testing using S. aureus clinical isolates obtained from PwCF. Utilization of a murine methicillin-resistant S. aureus (MRSA) pulmonary infection model further confirmed the in vivo anti-inflammatory and antibacterial effects of ATR-002. Finally, infection of wild-type and Mek2KO mice revealed that loss of MEK2 was host-protective during MRSA pulmonary infection by reducing neutrophil-mediated inflammation without altering bacterial clearance. In summary, this study highlights the therapeutic potential of targeting the MEK1/2 pathway to combat MRSA pulmonary infections.IMPORTANCEStaphylococcus aureus infections pose a significant burden on global healthcare systems. Community-associated transmission of methicillin-resistant S. aureus (MRSA) and the increasing prevalence of other drug-resistant S. aureus isolates limit therapeutic options to combat this opportunistic pathogen. Infection-induced inflammation is a significant driver of tissue damage, especially in cystic fibrosis pulmonary infections. However, therapeutic strategies that can reduce inflammation without compromising host defense and bacterial clearance mechanisms are lacking. This study investigates the dual anti-inflammatory and antibacterial effects of a MEK1/2 inhibitor as a therapeutic strategy to target both host and pathogen with a single compound. This work also identifies host MEK2 as a specific target that can be modulated to reduce inflammation without impairing host defense against MRSA pulmonary infection. Results from this study can inform future human clinical trials to evaluate the ability of the MEK1/2 inhibitor compound ATR-002 to both combat S. aureus infections and reduce inflammation that accompanies these infections.